Wife Battering: a Prospective Study in Sanandaj City, Iran - A Ghazizadeh (Tehran University of Medical Sciences, 2003)
To determine the prevalence of domestic physical violence against women and its associated factors in Sanandaj city, Iran, during the year 2000, this study was conducted. Random sampling of 1000 married women resident in Sanandaj city was conducted and underwent a standard interview as well as completed a 23-part questionnaire. 15 % and 38 % of the women had been assaulted by their husbands during the past year or in their marriage, respectively between 1 and 11 or more occasions. Economic problems were the most frequent cause of domestic quarrel, while there was a significant association between the husband's educational level and the violence against their wives (P=0.001).The physical violence against housewives was significantly more frequent than the employed ones .The husbands job was also significantly associated with their violence The existence of child or daughter in the family had a preventive role in domestic physical violence against women. Logit Regression Model for prediction of physical violence against women (Y) during the marriage was: "Y=0.014- 0.029 woman's age +0.199 numbers of children -0.238 man's education +0.589 woman's job ". This study confirms for Sanandaj city of Iran, the high frequency of physical violence against women by their husbands. Cultural education and supportive measures are essential to control that. Screening protocol for the detection of domestic violence in family planning Health Care System is recommended.